The correlation of starch composition, physicochemical and structural properties of different sorghum grains - Zhang, Kuangye; Ke, Fulai; Zhou, Hanling; Wang, Jiaxu; Ma, Zhenbing; Zhang, Fei; Wang, Yanqiu; Zhang, Zhipeng; Lu, Feng; Duan, Youhou; Wu, Han; Yang, Linlin; et al. (Frontiers in Plant Science, 2025)
The composition, structure, and physicochemical properties of starch in sorghum grains greatly influence the processing and quality of the final products. In this study, 19 sorghum lines were examined to analyze various starch-related characteristics. Correlation analysis of these key traits, revealed a significant correlation between amylose and amylopectin content. Amylopectin was identified as the primary component, averaging 80.75% of the starch content. The distribution of starch chain lengths, as well as the degrees of polymerization and branching, varied significantly among the sorghum lines, maintaining an equilibrium relationship between chain lengths. The size distribution of starch granules also varied among the lines, showing an overall positive correlation. Thermodynamic properties were positively correlated with each other, with correlation coefficients exceeding 0.614. Peak viscosity, trough viscosity, and final viscosity during the pasting process were highly correlated with the setback value, with correlation coefficients of -0.520, -0.651, and 0.618, respectively. 19 sorghum lines were classified into three categories: glutinous, japonica, semi-glutinous. Japonica sorghum exhibited superior thermal stability and viscoelasticity. This study elucidates the relationship between starch fractions, structure and physicochemical properties, providing a crucial theoretical foundation for optimizing sorghum processing for food and industrial applications.